Neural basis for inferring false beliefs and social emotions in others among individuals with schizophrenia and those at ultra-high risk for psychosis. (30th January 2017) - Takano, Yosuke; Aoki, Yuta; Yahata, Noriaki; Kawakubo, Yuki; Inoue, Hideyuki; Iwashiro, Norichika; Natsubori, Tatsunobu; Koike, Shinsuke; Gonoi, Wataru; Sasaki, Hiroki; Takao, Hidemasa; Kasai, Kiyoto; et al.
Abstract: Inferring beliefs and social emotions of others has different neural substrates and possibly different roles in the pathophysiology of different clinical phases of schizophrenia. The current study investigated the neural basis for inferring others' beliefs and social emotions, as individual concepts, in 17 subjects at ultra-high risk for psychosis (UHR), 16 patients with schizophrenia and 20 healthy controls. Brain activity significantly differed from normal in both the left superior temporal sulcus (STS) and the inferior frontal gyrus (IFG) in the schizophrenia group while inferring others' beliefs, whereas those of UHR group were in the middle of those in the schizophrenia and healthy-control groups. Brain activity during inferring others' social emotions significantly differed in both the left STS and right IFG among individuals at UHR; however, there was no significant difference in the schizophrenia group. In contrast, brain activity differed in the left IFG of those in both the schizophrenia and UHR groups while inferring social emotion. Regarding the difference in direction of the abnormality, both the UHR and schizophrenia groups were characterized by hyper-STS and hypo-IFG activations when inferring others' beliefs and emotions. These findings might reflect different aspects of the same pathophysiological process at different clinical phases of psychosis. Highlights: We investigated brain activity related to inferring others' belief and social emotion. People at ultra-high-risk, patients with schizophrenia and controls were compared. Clinical groups showed hyper superior temporal and hypo inferior frontalactivity. People at ultra-high-risk showed intermediate activity during inferring beliefs. Specificity & commonality to clinical stage were observed during inferring emotion.